Dispersal in a changing world: opportunities, insights and challenges - Tesson, Sylvie VM (Mov Ecol, 2013)
It has been long recognised that dispersal is an important life-history trait that plays a key role in the demography and evolution of populations and species. This then suggests that dispersal play a central role in the response of populations and species to ever-increasing global change, including climate change, habitat loss and fragmentation, and biological invasions. During a symposium held at Lund University (Sweden), the causes and consequences of dispersal were discussed, and here we provide an overview of the talks. As the discussions often gravitated towards the role and our understanding of dispersal in a changing world and given the urgent challenges posed by it, we place this overview in the context of global change. We draw and discuss four conclusions: (i) methodological advances provide opportunities for improved future studies, (ii) dispersal distances can be much greater than previously thought (examples in plants and vertebrates), but also much more restricted (examples in micro-organisms), (iii) dispersal is more dynamic than we often care to admit (e.g. due to individual variation, effects of parasites, variation in life history, developmental and evolutionary responses, community impacts), (iv) using results of dispersal research for detailed prediction of outcomes under global change is currently mostly out of reach – nevertheless, that should not stop us from showing the many negative consequences of global change, and how dispersal is often a limiting factor in adapting to this.